Clay Mineralogy of the Quaternary Lake Deposits of Peshawar Basin, At Jehangira, District Mardan, NWFP Pakistan - Khan, M. Javed; Ahmad, Waseem (Journal of Himalayan Earth Sciences, 1987)
X-ray Diffraction studies, of Post-Siwalik Quaternary lacustrine clay deposits exposed near Jehangira suggest the presence of illite, chlorite and montmorillonite. Illite and chlorite show regular and well-formed structure suggesting detrital origin. Whereas montmorillonite may have detrital and/or authigenic origin. If authigenic the depositional environments were alkaline and “non-aggressive". Mafic, ultramafic metamorphites of the Kohistan sequence and Main Mantle Thrust (=MMT) melange zone, and the schists of the Indo-Pakistan plate south of MMT me inferred as the ultimate source for these clay deposits.